A 110 W e-scooter wireless charger operating at 6.78 MHz with ferrite shielding - Kwan,CH; Arteaga,JM; Pucci,N; Yates,DC; Mitcheson,PD (IEEE, 2021)
This paper reports on the design, construction and integration of a wireless inductive charging solution for an electric scooter, operating at a frequency of 6.78MHz and providing an output power of 110 W. With the use of a push-pull Class EF inverter at the transmit end, as well as ferrite shielding and a voltage-doubler full-wave Class D rectifier at the receive end, this system achieved a DC-DC IPT efficiency of 69%-75% and exhibited good tolerance to misalignment at full charging power.